Raising an Awareness of World Englishes in ELT Classroom through Listening Journal - Budiyanto, Darmawan; Tridinanti, Gaya; Sari, Farnia (UNIB Press, 2024)
The use of listening journals is a useful pedagogy tool that will be applied in the classroom activities. Listening journal is a tool to promote the varieties of English of speakers from any cultural background. The aims of the study (1) to extend awareness of English varieties in the ELT class, (2) To extend listening journals reflected awareness of existing English varieties in ELT, (3) to describe students’ attitudes towards English varieties. The methodology is a qualitative research method. The sample of the study is the students of the English Education Study Program located in Palembang South Sumatera, Indonesia. The total sample are students of the English Education Study Program located in Palembang South Sumatera, Indonesia. The researchers use intake sampling techniques to select the sample. All the participants will be used as a sample. The interview and reflection will be measured to answer the problems of the study. Thematic analysis will be used to analyze the data.